Releasement and Seduction: Heidegger and Baudrillard on the Preservation of Illusion in the Epoch of Obscenity - Pasco, Marc Oliver D (Archīum Ateneo, 2021)
This work interfaces the philosophies of Jean Baudrillard and Martin Heidegger. It hopes to contribute to both Heideggerian and Baudrillardian scholarship by employing Baudrillardian ideas in more effectively describing the historical happening of the so-called withdrawal of Being from man, which preoccupied much of Heidegger’s body of work. The work argues that by re-visiting an earlier idea of Baudrillard, which he termed as seduction, one finds a possible way of navigating the obscenity of the current epoch of Being. Akin to Heidegger’s idea of Gelassenheit or releasement, Baudrillard’s concept of seduction invites one to allow the real to once again appear, no longer by way of subjective representation, but to let it appear in its very disappearance in hyperreality.